Beyond the dichotomy: understanding the overlap between atopic dermatitis and psoriasis - Li, Mengmeng; Wang, Jiangyi; Liu, Qingfeng; Liu, Youqing; Mi, Wenyao; Li, Wei; Li, Jingyi (Frontiers in Immunology, 2025)
Atopic dermatitis and psoriasis have traditionally been considered distinct inflammatory skin diseases with unique pathogenic mechanisms. However, accumulating evidence suggests significant overlap in their immunological pathways, metabolic features, and microbiome characteristics, challenging this conventional dichotomy. This review comprehensively examines the complex relationship between psoriasis and atopic dermatitis, with particular emphasis on their shared and distinct pathogenic mechanisms. We analyze the immunological networks, metabolic pathways, and microbial factors contributing to their development and progression. The review expands upon the disease spectrum hypothesis and discusses the nomenclature for conditions exhibiting features of both diseases. We critically evaluate the clinical and histopathological characteristics of concomitant psoriasis and atopic dermatitis, highlighting recent advances in molecular diagnostics for accurate disease differentiation. Importantly, we propose standardized diagnostic criteria for psoriasis dermatitis and examine current therapeutic strategies for managing overlapping conditions. Recent developments in targeted therapies and their implications for treatment selection are thoroughly discussed. By synthesizing current evidence and identifying knowledge gaps, this review provides insights into the complex interplay between psoriasis and atopic dermatitis, aiming to guide clinical decision-making and future research directions in this evolving field.